2016
DOI: 10.1073/pnas.1602960113
|View full text |Cite
|
Sign up to set email alerts
|

FAR-RED ELONGATED HYPOCOTYL3 activates SEPALLATA2 but inhibits CLAVATA3 to regulate meristem determinacy and maintenance in Arabidopsis

Abstract: Plant meristems are responsible for the generation of all plant tissues and organs. Here we show that the transcription factor (TF) FAR-RED ELONGATED HYPOCOTYL3 (FHY3) plays an important role in both floral meristem (FM) determinacy and shoot apical meristem maintenance in Arabidopsis, in addition to its well-known multifaceted roles in plant growth and development during the vegetative stage. Through genetic analyses, we show that WUSCHEL (WUS) and CLAVATA3 (CLV3), two central players in the establishment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 44 publications
(48 reference statements)
1
44
0
Order By: Relevance
“…The transcription factor FAR-RED ELONGATED HYPOCOTYL3 (FHY3), which is involved in photomorphogenesis, was shown to control the expression of the stem cell regulator CLAVATA3 (CLV3) in the shoot apical meristem (Li et al, 2016). In floral meristems, FHY3 controls determinacy by directly repressing CLV3 and by activating the E class gene SEPALLATA2.…”
Section: Control Of Floral Meristem Determinacymentioning
confidence: 99%
“…The transcription factor FAR-RED ELONGATED HYPOCOTYL3 (FHY3), which is involved in photomorphogenesis, was shown to control the expression of the stem cell regulator CLAVATA3 (CLV3) in the shoot apical meristem (Li et al, 2016). In floral meristems, FHY3 controls determinacy by directly repressing CLV3 and by activating the E class gene SEPALLATA2.…”
Section: Control Of Floral Meristem Determinacymentioning
confidence: 99%
“…1A-D). 16,17 While far1-2 produced normal siliques with 2 carpels, the siliques of fhy3-68 had 2.59 § 0 .7 carpels (n D 46), indicative of a weak FM determinacy defect of fhy3-68 ( Fig. 1C and E).…”
mentioning
confidence: 97%
“…16 Averysmall number of DEGs (29 up-regulated and 3 downregulated genes) were observedintheag-10sample,inlinewithitspointmutationandweak FM determinacy defects. The greater number of upregulated genes than down-regulated genes in fhy3 compared to Ler indicated that FHY3playsarepressiveroleinflowerdevelopment (Fig.3).Thisfinding was corroborated by the analysis of fhy3-68 ag-10 vs. ag-10 and fhy3-68 ag-10 vs. Ler.…”
mentioning
confidence: 98%
See 2 more Smart Citations